PENGARUH PERSENTASE BIODIESEL MINYAK JELANTAH - SOLAR TERHADAP KARAKTERISTIK PEMBAKARAN DROPLET - Andy Nugraha; Muhammad Nizar Ramadhan (INFO-TEKNIK, 2019)
Fossil fuels need to be replaced with alternative energy sources such as household waste, used cooking oil. This research utilizes household waste such as used cooking oil as an alternative fuel. In this research biodiesel used waste cooking oil mixed with diesel with a percentage of 50%: 50%, 60%: 40%, 70%: 30%, 80%: 20%, and 90%: 10%. The mixture of waste cooking oil and diesel biodiesel was then made into a 1 mm droplet grain, then a droplet combustion test was carried out. The test results show that the value of ignition delay time increases with increasing percentage of biodiesel used waste cooking oil. The burning rate value increases with the increase in the percentage of used waste cooking oil biodiesel. The temperature value increases with the increasing percentage of biodiesel used waste cooking oil. The maximum fire height value that can be achieved decreases with increasing percentage of used waste cooking oil biodiesel.